Synthesis and properties of flame-retardant reactive hot melt polyurethane adhesive. Issue 2 (17th January 2020) - Zhang, Wei; Xue, Weilan; Zeng, Zuoxiang; Li, Jiankun
Abstract: A novel liquid polyphosphonate polyol (DMDP) was synthesized from dimethyl methylphosphonate and 1, 6-hexanediol. Reactive hot melt polyurethane adhesives with high flame retardancy (HMPURs) were prepared from poly(tetramethylene ether glycol) (PTMG-2000), two kinds of poly(1, 4-butylene adipate) (PBA-2000 and PBA-3000) and DMDP or dimethyl methylphosphonate as well as tetrahydrofuran acrylate. Five specimens of flame-retardant HMPURs with different weight percent of DMDP (0, 2, 4 and 6 wt%) and dimethyl methylphosphonate (4 wt%) were obtained. The mechanical properties, thermal stability, flammability, and bonding strength of the specimens were investigated. The results show that with the increase of DMDP content, the elongation at break and tensile strength decrease slightly, and the flame retardancy of HMPURs is significantly improved with the limiting oxygen index (LOI) value increasing from 17.2 to 28.2. The incorporation of DMDP leads to a higher thermal stability of HMPURs at high temperature and more char yield at 650 °C. With the increase of DMDP content, the final bond strength of HMPURs on the same substrate changes little, but the green strength of HMPUR-6 on the same substrate is observably less than other samples. The performance of HMPUR with the reactive flame retardant is superior to that of HMPUR with the additive flame retardant. In addition, the corresponding flame-retardant mechanism of DMDP-containing HMPURs was investigated by pyrolysis-gas chromatography coupled to mass spectrometry (Py-GC/MS). The results indicate that the pyrolysis of the HMPURs releases phosphorus-containing fragments to play a flame retardant role.